The Effect of different Concentration of Fish Meat on Texture, Nutrition and Sensory of ‘Tahu bakso’ made from Tilapia (Oreochromish niloticus) - Tri Winarni Agustini; Yudhomenggolo Sastro Darmanto; Ima Wijayanti; Putu Har Riyadi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
Central Java is popular for soybean tofu and one of its diversification product is ‘tahu bakso’which is very famous in Central Java especially Semarang. Utilisation of nile fish meat can support fish protein intake by community as well as for promoting local protein resource. The aims of this study was to observe the effect of different concentration of fish meat on physical, chemical and sensory characteristic of ‘tahu bakso’. The parameters evaluated include texture (hardness, deformation, gel strength), proximate (protein, fat, carbohydrate, ash and water), and sensory (hedonic test) of the product resulted. This study used experimental laboratory by using Completely Randomised Design with Anova (p<0,05). The treatments covers: different concentration of fish meat (30%, 40% and 50%). Treatment with highest hardness and gel strength was performed by 30% concentration with the value of 530.88 g.cm. Whereas treatment 40% concentration has highest deformation of 23.47 mm, and has no significant different to 50% concentration. Based on analysis of variance, different concentration of fish meat gave significant effect on characteristic of proximate especially on protein and fat (p<0.05) but has no significant effect on water and ash content (p>0.05). Different concentration of fish meat has no significant effect on hedonic of ‘tahu bakso’ resulted. Overall ‘tahu bakso’ made from nile meat with 50% concentration is considered to be the most preferred by panelist, but the overall value has no significant different to 40% concentration. Therefore, it is concluded that concentration 40% of fish meat is considered as the best treatment for producing ‘tahu bakso’ with respect to texture, nutrition, sensory attributes.